Multifunction Yoga Mat / Wan Nur Mawaddah Wan Rusli - Wan Rusli, Wan Nur Mawaddah (2020)
Kugona Enterprise is a company that sells sports product and equipment. Most of the products were create to those who are usually involves in physical activity. One of our products is Multifunction Yoga Mat. This Multifunction Yoga Mat eases peoples where the yoga mat is attached with the speaker and also electronic devices holder. Target market for this Multifunction Yoga Mat is created for sports person and Yoga practitioner. This product could attract interest of people to buy because as for now, there is no yoga mat that attached with the speaker and electronic devices as what we created and innovate. We also provide mat strap to ease the customer to carry the mat. This product will give many benefits to athlete, coach and yoga practitioner who have problems or difficulties during performing physical activity. This product will lessen their burden because they don’t need to bring a big speaker and they can put their electronic devices at the holder while they following the demo in the smartphone. We offer the best and cheapest price for our potential customer. We will ensure that everyone will afford to buy this product.